Narrative Inquiry as a nursing research methodology: reflection on ethical considerations - Inês Frade; Vanda Marques Pinto; Luisa D'Espiney (Associação de Enfermagem Oncológica Portuguesa, 2024)
Introduction: There is an emerging propensity to use narrative inquiry as a nursing research methodology. The narrative inquiry aims to understand experiences and reveal the meaning of individual experiences providing crucial knowledge. The relationship between the nurse researcher and the participant is especially relevant in narrative inquiry. Purpose: To discuss ethical conduct in narrative inquiry and examine specific ethical issues at different stages of the narrative inquiry process in nursing research. Methods: Critical reflection supported by scientific evidence. Results: The relational component and the proximity with the participants imply greater responsibility and a strict ethical attitude. Critical ethical issues in research planning, data collection, composing field texts, data analysis and interpretation, and results presentation must be considered and respected in narrative inquiry. Conclusion: Engagement in this methodology involves scrupulous ethical conduct in the relationship with the participants and in using their narratives, respecting scientific rigour.